2020
DOI: 10.3389/fnagi.2020.00027
|View full text |Cite
|
Sign up to set email alerts
|

The Density of Perineuronal Nets Increases With Age in the Inferior Colliculus in the Fischer Brown Norway Rat

Abstract: Age-related hearing loss, one of the most frequently diagnosed disabilities in industrialized countries, may result from declining levels of GABA in the aging inferior colliculus (IC). However, the mechanisms of aging and subsequent disruptions of temporal processing in elderly hearing abilities are still being investigated. Perineuronal nets (PNs) are a specialized form of the extracellular matrix and have been linked to GABAergic neurotransmission and to the regulation of structural and synaptic plasticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 114 publications
(173 reference statements)
2
20
0
Order By: Relevance
“…It should be noted that several studies failed to detect differences in PNN abundance in clinical AD [202][203][204][205], and this may be partly attributable to the brain region under investigation or the method of PNN labeling used. While changes with non-diseased aging are less clear [90,[206][207][208], we and others have found age-related reductions in PNN density in older animals [90,193,208,209], and discrepancies across studies may depend on the inclusion of both sexes and the brain region(s), mouse strain, and/or model organism being studied.…”
Section: Perineuronal Netsmentioning
confidence: 57%
“…It should be noted that several studies failed to detect differences in PNN abundance in clinical AD [202][203][204][205], and this may be partly attributable to the brain region under investigation or the method of PNN labeling used. While changes with non-diseased aging are less clear [90,[206][207][208], we and others have found age-related reductions in PNN density in older animals [90,193,208,209], and discrepancies across studies may depend on the inclusion of both sexes and the brain region(s), mouse strain, and/or model organism being studied.…”
Section: Perineuronal Netsmentioning
confidence: 57%
“…Two studies have shown circadian/diurnal changes, with higher numbers or intensity of PNNs in the dark phase in rodents (Pantazopoulos et al, 2020 ; Harkness et al, 2021 ). Given that PNNs are altered in many ways throughout central nervous system development, and their maturation is brain region-specific and generally coincides with the end of critical periods of plasticity (for a recent review see Carulli and Verhaagen, 2021 ), it is not surprising that numerous studies have also demonstrated changes in PNNs or their composition during aging (Tanaka and Mizoguchi, 2009 ; Karetko-Sysa et al, 2014 ; Brewton et al, 2016 ; Foscarin et al, 2017 ; Richard et al, 2018 ; Ueno et al, 2019 ; Mafi et al, 2020 ). Overall, changes in PNNs and PV neurons after physiological stimuli appear to be specific to the physiological stimulus, brain region, and the circuits in which PNN-surrounded neurons are embedded.…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%
“…FBN rats have a long life span and lower tumour load than other commonly used rat ageing models. They have been characterized as a rat model of ageing (Cai et al 2018), and age-related changes in their central auditory structures have been extensively studied (Caspary et al 2008;Caspary & Llano, 2019;Mafi et al 2020).…”
Section: Ethical Approvalmentioning
confidence: 99%